Sosialisasi Penanganan Kekerasan Seksual Berbasis Budaya Lokal di Kelurahan Lembang, Majene - Pratiwi, Andi Dewi; Yasim, Sulastri; Nuraliah, Dewi; Anwar, Muh. Chaerul; IK, Riady (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aimed to enhance the understanding of the people in Lembang Subdistrict, Majene Regency, regarding the culturally based handling of sexual violence. Through a participatory socialization approach, the activity involved various community elements, including women's and youth groups, to build collective awareness in preventing and addressing sexual violence. The methods used included counseling sessions, interactive discussions, and case handling simulations that integrated customary mechanisms with the formal legal system. This approach enabled participants to understand the steps of reporting and the significant role of traditional institutions in mediation and rehabilitation. Evaluation results showed a significant increase in community knowledge and readiness in dealing with cases of sexual violence, as well as the formation of communication networks between the community and related institutions. The activity recommends the need for culturally based approaches as preventive strategies to create a safe and inclusive environment for all community members.